Senior High School Students' Perceptions about the Use of Smartphones as English Learning Media - Sri Damayanti; Irwan Irwan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
in this research, the researcher focused on the students’ perception on the use of smartphone as an English learning media especially for Indonesian Secondary High School (SMA) students. This is the type of concurrent mix (combination) research whose qualitative method is more highly used than its quantitative method. Data collecting techniques in this research are survey study with Likert-scaled questionnaire, direct observation, and interview. The survey results then classified and ranked statistically to know the frequency level of the smartphone use in learning English as well as to encounter students’ perception on it. To present more comprehensive data and information, the research result then quantitatively illustrated in an appropriate chart or diagram, and qualitatively described in narrative form. The implication about the use of smart phone is presented as well to give more insightful view for the students or teachers about how to maximize the advantages of smart phone media in learning English.